High EMSY expression defines a BRCA‐like subgroup of high‐grade serous ovarian carcinoma with prolonged survival and hypersensitivity to platinum. Issue 16 (2nd June 2019) - Hollis, Robert L.; Churchman, Michael; Michie, Caroline O.; Rye, Tzyvia; Knight, Laura; McCavigan, Andrena; Perren, Timothy; Williams, Alistair R. W.; McCluggage, W. Glenn; Kaplan, Richard S.; Jayson, Gordon C.; Oza, Amit; et al.
Abstract : Background: Approximately half of high‐grade serous ovarian carcinomas (HGSOCs) demonstrate homologous recombination repair (HR) pathway defects, resulting in a distinct clinical phenotype comprising hypersensitivity to platinum, superior clinical outcome, and greater sensitivity to poly(adenosine diphosphate‐ribose) polymerase (PARP) inhibitors. EMSY, which is known to be amplified in breast and ovarian cancers, encodes a protein reported to bind and inactivate BRCA2. Thus, EMSY overexpression may mimic BRCA2 mutation, resulting in HR deficiency. However, to our knowledge, the phenotypic consequences of EMSY overexpression in HGSOC patients has not been explored. Methods: Here we investigate the impact of EMSY expression on clinical outcome and sensitivity to platinum‐based chemotherapy using available data from transcriptomically characterized HGSOC cohorts. Results: High EMSY expression was associated with better clinical outcome in a cohort of 265 patients with HGSOC from Edinburgh (overall survival multivariable hazard ratio, 0.58 [95% CI, 0.38‐0.88; P = .011] and progression‐free survival multivariable hazard ratio, 0.62 [95% CI, 0.40‐0.96; P = .030]). Superior outcome also was demonstrated in the Medical Research Council ICON7 clinical trial and multiple publicly available data sets. Patients within the Edinburgh cohort who had high EMSY expression were found to demonstrate greater rates of complete response to multiple platinum‐containing chemotherapy regimens (radiological complete response rate of 44.4% vs 12.5% at second exposure; P = .035) and corresponding prolonged time to disease progression (median, 151.5 days vs 60.5 days after third platinum exposure; P = .004). Conclusions: Patients with HGSOCs demonstrating high EMSY expression appear to experience prolonged survival and greater platinum sensitivity, reminiscent of BRCA ‐mutant cases. These data are consistent with the notion that EMSY overexpression may render HGSOCs HR deficient. Abstract : Patients with high‐grade serous ovarian carcinomas demonstrating high expression levels of EMSY appear to experience prolonged survival and hypersensitivity to multiple lines of platinum‐based chemotherapy. These data support the notion that overexpression of the gene product of EMSY, which is reported to bind and inactivate BRCA2, may mimic the phenotype conferred by BRCA mutation.